Pemanfaatan Kecerdasan Buatan Sebagai Media Pengembangan Literasi Digital Guru Bahasa Inggris di SMP di Kabupaten Lombok Barat - Untung Waluyo; Eka Fitriana; Hartati Suryaningsih; Nurul Fitriah; Wisnu Ardiansyah; Henny Soepriyanti (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The goal of this community service program was to assist teachers to learn more about technology and get better at using AI tools like ChatGPT, QuillBot, and Canva AI to make engaging learning materials. The program used a model of workshops where everyone could participate, followed by continuing mentoring and self-evaluation. Twenty English teachers from the Musyawarah Guru Mata Pelajaran (MGMP) network went to SMPN 4 Gunung Sari for mixed-type training. Surveys, observations, and conversations were used to gather information. The results show that teachers' trust and ability to use AI in English Language Teaching (ELT) has grown significantly. Participants made lesson plans and teaching tools that used AI and shared the best ways to do things through digital communities. Teachers liked the practical method and were ready to keep using AI tools, even though there were some problems, like not enough infrastructures and not enough time for practice. This program shows that learning how to use AI can change the way teachers do their jobs and help schools build a culture of digital innovation that lasts. It is suggested that a training of trainers’ model be used to make the program more impactful to facilitate the MGMP community. Thus, it will create a chain effect that helps teachers become more independent and keeps the training going in their local areas.